KAJIAN ADSORPSI Ag(S2O3)2 3- DALAM LIMBAH FOTOGRAFI PADA ADSORBEN KITIN DAN ASAM HUMAT TERIMOBILISASI PADA KITIN - Khoerunnisa, Fitri; Santosa, Sri Juari; Kunarti, Eko Sri (Jurnal Pengajaran MIPA, 2007)
This work was started with isolation of humic acid from peat soil and chitin from crab shell, immobilization of humic acid on chitin, and characterization of adsorbents of C and HAC. Optimum condition was studied by interacting the adsorbents with Ag(S2O3)2 3- in a synthetic solution on various of pH from 2 to 10. Adsorption rate was studied by interacting the adsorbent with Ag(S2O3)2 3- in the synthetic solution on various time from 2 to 120 minutes. The determination of the energy and the capacity of adsorption were studied by interacting the adsorbent with Ag(S2O3)2 3- on various initial concentration from 2 to 75 ppm. Moreover, the mechanism of adsorption was studied by applying a sequential desorption using H2O, Na2EDTA 0.1 M, KSCN 0.5 M, and KOH 1 M. The adsorption of Ag(S2O3)2 3- in photography wastewater on C and on HAC were studied at the same condition as obtained for the synthetic solution. The result showed that pH 2 was the optimum adsorption condition for Ag(S2O3)2 3- in the synthetic solution on both C and HAC adsorbents. Ag(S2O3)2 3- in the synthetic solution was chemically adsorbed on C and on HAC, involving energy adsorption of 22.74–23.30 kJ/mole, respectively. Adsorption of Ag(S2O3)2 3- on C was faster than that on HAC with the rate constants for adsorbent C and HAC were 73 x 10-4 and 46 x 10-4 minute-1 , respectively. Adsorption capacity of Ag(S2O3)2 3- on C and on HAC were 2.107 x 10-4 and 1.818 x 10-4 mole/g, respectively. The amount of Ag(S2O3)2 3- in photography wastewater that was adsorbed on C and on HAC were 13.52 and 12.47 mg/L, respectively. The hydrogen bonding and ion exchange were the dominant mechanism of adsorption.